More than meets the eye ; Save the chapel ; Balicasag [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Interview with Ka Roger, NPA Melito Glor Command Spokesman about graft and corruption raps against Ka Hector. Twenty years after businessman John Gokongwei bought a Jesuit owned real estate property in Ermita, he is finally claiming it for commercial purposes. The Probe Team takes a break in the newed diving haven off the Southeastern tip of Bohol.